MOG-antibody-associated transverse myelitis with the H-sign and unusual MRI enhancement: a case report and literature review - Zhang, Lu; Feng, Chuan; He, Ling; Huang, Shi-Yu; Liu, Xin-Yin; Fan, Xiao (Frontiers in Pediatrics, 2024)
Transverse myelitis is the second most common symptoms in myelin oligodendrocyte antibody-associated diseases (MOGAD), causing obvious clinical manifestation. T2-hyperintense lesions mainly restricted to the gray matter in the spinal cord on axial magnetic resonance imaging, produce the H-sign, which is thought to be the typical finding of MOGAD. Contrast enhancement can be observed in some cases of myelin oligodendrocyte antibody-associated transverse myelitis (MOG-TM). However, reports on the enhancement pattern associated with the H-sign are rarely seen. In this report, we describe a case of pediatric MOG-TM in which the H-sign was observed without enhancement, while the surrounding white matter exhibited enhancement. This pattern contradicts the previously observed gray matter involvement. Then we reviewed the literatures of myelin oligodendrocyte antibody-positive myelitis to focus on the neuroimaging features and discuss the implications of our finding.